Semisynthetic and Enzyme‐Mediated Conjugate Preparations Illuminate the Ubiquitination‐Dependent Aggregation of Tau Protein. Issue 16 (28th February 2020) - Munari, Francesca; Barracchia, Carlo G.; Franchin, Cinzia; Parolini, Francesca; Capaldi, Stefano; Romeo, Alessandro; Bubacco, Luigi; Assfalg, Michael; Arrigoni, Giorgio; D'Onofrio, Mariapina
Abstract: In the brain of individuals with Alzheimer's disease, the regulatory protein ubiquitin is found conjugated to different lysine residues of tau protein assembled into pathological paired helical filaments. To shed light on the hitherto unexplored ubiquitination‐linked conformational transitions of tau, the availability of in vitro ubiquitin conjugation methods is of primary importance. In our work, we focused on the four‐repeat domain of tau and assembled an enzymatic machinery formed by UBE1, Ubc13, and CHIP enzymes. The enzymatic reaction resulted in monoubiquitination at multiple sites, reminiscent of the ubiquitination pattern observed in vivo. We further exploited chemoselective disulfide coupling reactions to construct three tau regioisomers with site‐specific monoubiquitination. Protein aggregation experiments revealed that the multiple enzyme‐derived products were unable to convert into amyloid fibrils, while the semisynthetic conjugates exhibited diverse capability to form filaments. This study contributes novel insight into the effects of a key post‐translational modification on aberrant protein self‐assembly. Abstract : Shedding light on Alzheimer : Semisynthetic and enzyme‐based conjugation methods were applied to interrogate, at the molecular level, the effects of ubiquitin modification on aberrant aggregation of tau protein in neurodegeneration.